Trichoderma sp. Biopesticide Application Against Vegetative Biomass and Potato (solanum tuberosum) - Sutarman Sutarman; Vicky Prasetya Putra (Universitas Muhammadiyah Sidoarjo, 2018)
This study aims to examine the biopesticide application of Trichoderma sp. to control leaf blight on potatoes. This research was conducted at the campus microbiology laboratory of Sidoarjo Muhammadiyah University, Gelam village, Sidoarjo district temple district and Tulungrejo village land, Bumiaji Sumberbrantas, Batu East Java, from July to September 2018. This study was arranged in a Completely Randomized Design (CRD) with 4 treatments and repeated 8 times so that 32 experimental units were obtained. The variables observed were stover wet weight, stover dry weight, total tuber weight, and rotten tuber weight. Data were analyzed by various ANOVA analysis followed by BNJ test at 5% level. The results showed that Trichoderma biopesticide had no significant effect on the weight of the stover of potato plants both wet and dry, and on the total tuber weight. But it has a difference in reducing rotten tubers.